PENINGKATAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD INPRES KOKWARI - Henderjeta Mose; Samuel P. Ritiauw; Franshiene Rumtutuly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the application of the Jigsaw Type cooperative learningmodel to improve the learning outcomes of fifth grade students of SD InpresKokwari. This research is a class action research (PTK), the subject of this researchis the fifth grade students of SD Inpres Kokwari totalling 15 students, the object ofresearch is the learning outcomes of students by using the Jigsa Type Cooperativelearning model, while the instruments used are observation sheets and tests. Thedata analysis technique used was qualitative and quantitative data analysis. Theresults showed that the learning outcomes of fifth grade students of SD InpresKokwari in cycle I and cycle II increased after implementing learning activities usingthe Jigsaw Tips Cooperative learning model. The increase in learning outcomes isevidenced by the average score in the initial test of 60, cycle I increased to 68.6 andcycle II increased to 82.6